Sharing is Caring – Care workers’ employment bargain and the National Minimum Wage - Stabryla, Kinga (Kent Law Review, 2018)
It is undoubtingly noticeable that care workers' employment rights are currently prominent in the news and raise important social, market and legal concerns of equality and fairness. They stimulate debates on the consequences of the legal position on the 'wage-work bargain' of care workers and the national minimum wage laws are central to this. <span style="line-height: 107%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">It can be said that national minimum wage (NMW) underpayments stem from laws which define social structures and attitudes about care giving. As such, the core substance of NMW regulations will be analysed to define how and why this issue exists and what is the impact. Inevitably, socio-legal issues about the gendered workforce, multi-level control of the industry and economics (the ageing population, social capital and market logics) will serve as perspectives of criticism to the current position of law on care work and the NMW.